2021
DOI: 10.1007/s41669-021-00306-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns, Outcomes, Resource Utilization and Costs in Treatment-Resistant Major Depressive Disorder: PATTERN, a Retrospective Cohort Study in Belgium

Abstract: Objective Treatment-resistant depression (TRD), a subgroup of major depressive disorder (MDD) that does not adequately respond to treatment, has a substantial impact on the quality of life of patients and is associated with higher medical and mental health care costs. This study aimed to report real-world treatment patterns, outcomes, resource utilization, and costs in the management of TRD by psychiatrists in Belgium. Methods We conducted a retrospective, non-intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Likewise, over a 2 year follow-up period, Gillain and colleagues found that of 95 patients who achieved response or remission, 61% relapsed. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, over a 2 year follow-up period, Gillain and colleagues found that of 95 patients who achieved response or remission, 61% relapsed. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In the context of TRD, a short time horizon may underestimate the cost effectiveness of an intervention by failing to account for smaller incremental improvements in mental health (accruing substantially with a longer horizon), or the improvements that persist beyond the evaluation horizon – for example, MDD patients receiving cognitive therapy have been found to exhibit reduced relapse rates for up to 6 years ( 78 ). Conversely, bearing in mind the highly recurrent nature of TRD over periods of up to 36 months ( 105 , 106 ), cost effectiveness might be overestimated through censoring of relapse or recurrence events. Extrapolation implicitly introduces additional uncertainty into the model, but one must balance the impact of that additional uncertainty on results against the benefits of decision support that reflects the longer-term costs and consequences of the intervention in question.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the search strategy are reported in the ESM (Appendix 3). The study by Taipale and colleagues [ 33 ] reported 100.1 days lost for TRD in a period of 8 months; a European study reported a working time loss of 57% [ 27 ], while another study conducted in Belgium [ 34 ] showed an average number of calendar days ‘not working’ per month of 22.2 during a major depressive episode. A study conducted in Italy [ 35 ] reported a mean of 42 working days lost per year for patients with TRD, while a study conducted in the UK showed an overall work impairment of 51% for those patients [ 36 ].…”
Section: Methodsmentioning
confidence: 99%